Surgical versus medical treatment for infective endocarditis in patients on dialysis: a systematic review and meta-analysis. Issue 1 (31st December 2022) - Ting, Sze-Wen; Chen, Jia-Jin; Lee, Tao-Han; Kuo, George
Abstract: Infective endocarditis (IE) is a serious infection and causes significant morbidity and mortality. However, the benefit of surgery for endocarditis besides antibiotic treatment in dialysis patients remains controversial. We performed a systematic review of studies published between 1960 and February 2022. Meta-analysis was conducted with a random-effects model to explore the in-hospital, 30, 60, 90, 180-d, and 1-year mortality rates in adult dialysis patients with IE. Sensitivity analysis, subgroup analysis, and meta-regression were performed to explore potential sources of heterogeneity. Confidence of evidence was evaluated by the GRADE system. Thirteen studies were included. The pooled odds ratio of in-hospital mortality was 0.62 (95% confidence interval [CI]: 0.30–1.28, p  = .17), with moderate heterogeneity ( I 2 = 62%, p  < .01). Three studies reported 30-d mortality, and the pooled odds ratio for surgery compared with medical treatment was even lower (0.36; 95% CI: 0.22–0.61, p  < .01), with low heterogeneity ( I 2 = 0%, p  = .86). With studies on fewer than 30 patients excluded, the sensitivity analysis revealed a low odds ratio of in-hospital mortality for surgery versus medical treatment (0.52; 95% CI: 0.27–0.99, p  = .047), with moderate heterogeneity ( I 2 = 63%, p  < .01). Subgroup analysis revealed no significant differences between any two comparator subgroups. Based on a very low strength of evidence, compared with medical treatment, surgical treatment for IE in patients on dialysis is not associated with lower in-hospital mortality. When studies on fewer than 30 patients were excluded, surgical treatment was associated with better survival.